2021
DOI: 10.1093/ijnp/pyab079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Partial M1 Muscarinic Cholinergic Receptor Agonist CDD-0102A on Stereotyped Motor Behaviors and Reversal Learning in the BTBR Mouse Model of Autism

Abstract: Background Autism spectrum disorders (ASD) are a set of neurodevelopmental disorders marked by a lack of social interaction, restrictive interests and repetitive behaviors. There is a paucity of pharmacological treatments to reduce core ASD symptoms. Various lines of evidence indicate that reduced brain muscarinic cholinergic receptor activity may contribute to an ASD phenotype. Methods The present experiments examined whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 49 publications
0
21
1
Order By: Relevance
“…Acute and subchronic treatment as well as an intrastriatal infusion of CDD-0102A attenuated elevated digging behavior in BTBR mice. More specifically, systemic injections of CDD-0102A at a 1.2 mg/kg dose significantly attenuated elevated self-grooming behavior and digging behavior . In all cases, CDD-0102A at the 1.2 mg/kg dose reduced stereotyped motor behavior in BTBR mice without affecting overall locomotor activity, indicating that the drug effect at 1.2 mg/kg was selective to the stereotyped motor behavior.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Acute and subchronic treatment as well as an intrastriatal infusion of CDD-0102A attenuated elevated digging behavior in BTBR mice. More specifically, systemic injections of CDD-0102A at a 1.2 mg/kg dose significantly attenuated elevated self-grooming behavior and digging behavior . In all cases, CDD-0102A at the 1.2 mg/kg dose reduced stereotyped motor behavior in BTBR mice without affecting overall locomotor activity, indicating that the drug effect at 1.2 mg/kg was selective to the stereotyped motor behavior.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, targeting muscarinic receptors may be an effective approach for modifying altered glutamate and/or GABAergic signaling that underlies an autism phenotype. A recent study in BTBR mice examined the effects of the partial M 1 muscarinic agonist CDD-0102A on digging behavior in the nesting removal test . Acute and subchronic treatment as well as an intrastriatal infusion of CDD-0102A attenuated elevated digging behavior in BTBR mice.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is extensive evidence that frontal-striatal circuits across mammalian species support cognitive flexibility ( Stelzel et al, 2013 ; Oemisch et al, 2019 ; Williams and Chritakou, 2021 ) and that this circuitry may be altered in multiple disorders that exhibit cognitive inflexibility ( Marsh et al, 2014 ; D’Cruz et al, 2016 ; Langley et al, 2021 ). Both preclinical and clinical studies suggest that the striatum is critical for reliably executing a new choice pattern during reversal learning ( Haluk and Floresco, 2009 ; Hill et al, 2015 ; Sleezer and Hayden, 2016 ; Grospe et al, 2018 ) and treatments that improve probabilistic reversal learning can rescue probabilistic reversal learning deficits in mouse models of autism when infused directly into the dorsomedial striatum by reducing regressive errors ( Amodeo et al, 2017 ; Athnaiel et al, 2022 ). Further, brain imaging studies in humans indicate that typically developing subjects exhibit significant activation in frontal cortex and ventral striatum when outcomes are uncertain in a reversal learning test while ASD individuals do not display activation in this brain circuitry under the same test conditions ( D’Cruz et al, 2011 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite cognitive flexibility impairments commonly reported in FXS individuals ( Hooper et al, 2008 , 2018 ; Schmitt et al, 2019b ; Weber et al, 2019 ), there is limited understanding of what underlying cognitive processes are altered that contribute to a cognitive flexibility deficit in FXS. This is critical to identify as numerous preclinical studies in rodents have shown that pharmacological treatments that improve cognitive flexibility, i.e., set-shifting or reversal learning, modify specific processes by either reducing perseveration of a previously learned strategy or increasing sensitivity to positive reinforcement ( Boulougouris et al, 2008 ; Brown et al, 2012 ; Phillips et al, 2018 ; Dunn et al, 2020 ; Wilkinson et al, 2020 ; Athnaiel et al, 2022 ). In addition, while the absence of FMRP has been modeled in the Fmr1 -knockout (KO) mouse, which can display behavioral flexibility deficits ( Van Dam et al, 2005 ; McNaughton et al, 2008 ; Casten et al, 2011 ; Dickson et al, 2013 ; Kazdoba et al, 2014 ; Nolan and Lugo, 2018 ; Vershkov et al, 2022 ), a further challenge is developing cognitive flexibility tests that have a significant translational component so that more direct comparisons can occur between clinical and preclinical findings, as well as improving the probability that treatments found effective in preclinical experiments successfully translate to the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of pharmacological manipulations on excessive self-grooming behaviors of BTBR mice have fault to archive consistent effects, including the use of cholinergic, glutaminergic, or serotonergic agents [53,[55][56][57]. Highly complicated, sequential organization of grooming (and related defensive) behaviors raises a hypothesis that various neural circuits regulating discrete components of complex behaviors (e.g., motor, strategy, and sequencing) are involved.…”
Section: Oxt Circuit-dependent Regulation Of Socio-emotional Behaviormentioning
confidence: 99%